Pengembangan Bahan Ajar Handout Berbasis Pendekatan Keterampilan Proses Materi Data Diri Peserta Didik dan Lingkungan - Zeny Fitriyatul Munarohmaniyah; Nur Aulia Dewi; Romaniyah Romaniyah; Muh Syauqi Malik (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This research is in the background with the characteristics of students during the learning activity process. This leads to reduced student activity and participation in learning. This research was conducted with the aim of helping educators to develop teaching materials with a process skills approach to train students to be active and creative in the learning process. The teaching materials developed are in the form of Handout teaching materials based on the Process Skills approach on personal data material and angular sizes on flat buildings in grade IV Elementary School. Making questions on this teaching material is included in the HOTS (Higer Order Thingking Skill) category. So that it can improve critical thinking skills in students. The development method used is ASSURE with stages of analyzing student characteristics, determining goals, choosing learning methods, media, and strategies, using learning materials, evaluating and revising